Biological aspects of Head and Neck Cancer - Souza de Oliveira, Nikael; Rech, Nathália (Revista Interdisciplinar de Ciência Aplicada, 2023)
Cancers are genetic origin pathologies, caused by cell cycle anomalies, with two main groups of genes related to their development: Oncogenes and tumor suppressor genes. Head and neck cancer is the name given to a heterogeneous group of cancers that occur above the collarbone region. These pathologies are aggressive and disfiguring, with a high mortality rate due to late diagnosis. Many risk factors are associated with development of this pathology, being smoker, alcoholism and HPV infection the main. The last one, is so important, that oropharyngeal cancer received a new staging classification for patients HPV-postive and patients HPV-negative. It’s understood that earlier the cancer is diagnosed, better is the cure chance. For that reason, more studies in this area are important.